2013
DOI: 10.1126/science.1231097
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Common Mechanism of SIRT1 Regulation by Allosteric Activators

Abstract: A molecule that treats multiple age-related diseases would have a major impact on global health and economics. The SIRT1 deacetylase has drawn attention in this regard as a target for drug design. Yet controversy exists around the mechanism of sirtuin-activating compounds (STACs). We found that specific hydrophobic motifs found in SIRT1 substrates such as PGC-1α and FOXO3a facilitate SIRT1 activation by STACs. A single amino acid in SIRT1, Glu230, located in a structured N-terminal domain, was critical for act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
536
4
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 530 publications
(568 citation statements)
references
References 30 publications
20
536
4
4
Order By: Relevance
“…2 C and D and Fig. S2B) (P > 0.05, MWU), further confirming the specificity of SRT2183 triggering SIRT1 activation (45,46). These data indicate that SIRT1 prompts significant redistribution of nuclear NADH.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…2 C and D and Fig. S2B) (P > 0.05, MWU), further confirming the specificity of SRT2183 triggering SIRT1 activation (45,46). These data indicate that SIRT1 prompts significant redistribution of nuclear NADH.…”
Section: Resultssupporting
confidence: 70%
“…In vitro studies indicate that enzymatic inactivation of SIRT1 results in a decreased affinity for its substrates, whereas its activation promotes lowering the K m for substrates (46,49,50). We sought to explore whether SIRT1 binding to substrates could be modulated by its activation through nuclear metabolism in living cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The murine MFN2 contains five putative lysine (Lys) residues (K37, K215, K357, K655, and K662) that meet the criterion as deacetylation sites of SIRT1 (Figure 6a) (Hubbard et al., 2013). To test the relative importance of these Lys residues in their interaction with SIRT1, deletion and point mutants of MFN2 were constructed and expressed in HEK293T cells.…”
Section: Resultsmentioning
confidence: 99%
“…34 A recent and elegant study has shed some light on the debate and demonstrated that SIRT1 is directly activated by RSV, through an allosteric mechanism. 64 However, this effect may be dependent on the cell type, the dose of RSV used or other factors related to the specific context. In our experimental in vitro conditions, RSV inhibited ROS production independently of SIRT1, which may be attributed to the polyphenolic nature of the compound, exhibiting well-known ROS scavenger properties.…”
Section: Discussionmentioning
confidence: 99%